Reviewing of the Simulation Models in Cost Management of the Construction Projects - Al-Zwainy, Faiq Mohammed Sarhan; Amer, Reem; Khaleel, Tareq (Salehan Institute of Higher Education, 2016)
Simulation and computational techniques cover a variety of aspects also had proved its feasibility in construction management as whole, so it had adopted by a lot of researches during the last decades with rapid progress. The current study presents a focused review about construction cost simulation using, and provides an overview of such advancements achieved between 1990 and 2016 in construction management sector. This paper focuses specifically on many different topics including construction cost simulation, simulation modelling concept, steps of simulation conducting, simulation purposes, simulation advantages and disadvantages, etc.Â Major advances in construction cost simulation area are highlighted, as well as the trends for development and application. Over the selected study period, there has been a substantial increase in the use of high-fidelity simulation in construction cost management.